Boosting the profitability of micro and small businesses through the strategic use of financial tools - Diaz Cubas, Sandro (LACCEI, 2025)
This study aimed to determine the relationship between the use of financial tools and profitability in MSMEs in the La Perla market, located in Chimbote, Peru. The research was conducted using a quantitative approach, with a non-experimental cross-sectional design and correlational scope. Validated questionnaires were administered to all 54 formal MSMEs operating in this market, yielding results that demonstrate a highly significant relationship between the dimensions of financial analysis, financial planning, and use of the cash budget and profitability, achieving Spearman coefficients between 0.876 and 0.979. Among the most relevant findings, it is worth highlighting that the use of the cash budget showed the strongest relationship with profitability, allowing for the optimization of liquidity and the anticipation of contingencies, while financial planning strengthened resource control and financial analysis facilitated more accurate strategic decisions. Overall, the statistical analyses demonstrated that financial tools are crucial for improving the profitability of MSMEs, reinforcing their sustainability in a highly competitive environment. In conclusion, the systematic use of these tools significantly contributes to SMEs in the La Perla market strengthening their position in the local market and better facing the financial challenges of 2024.